O trabalho da coordenadora pedagógica junto às docentes de turmas de creche em um centro de educação infantil (CEI) municipal de Fortaleza - Lopes, Ana Kilvia Oliveira (2019)
In order to Early Childhood Education reach the goal established in current legislation (child’s integral development of children up to five years and eleven months old in terms of their physical, psychological, intellectual and social aspects which complements the family and community action), it is necessary that the work of all those involved in the educational process be aimed towards this purpose. The present research focuses on the work developed by the Pedagogical Department (PD) in this direction seeking to understand the perspective of several segments that comprise an Early Childhood Education Unit (ECEU) of the municipality of Fortaleza, Brazil, regarding actions involving nursery teachers. The main theoretical subsidies with regard to education, early childhood education, and with regard to the work of the PD in this stage were sought in Rocha (1999), Faria (1999), Bondioli (2004), Marx (2004), Cerisara, (2005), Paro (2016), Vasconcellos (2009), Domingues (2014). For the fieldwork the qualitative research was adopted and it was mainly used observations from the daily life of the ECEU, and semi-structured interviews with three nursery teachers for data collection. The observations showed a great amount of attributions of the PD, sole manager in the ECEU, and mostly the occurrence of managerial issues to the detriment of a pedagogical work with the teachers. This wide gap is larger in relation to nursery teachers due to the direct interference of a policy of results which is adopted within the municipality, and that requires the PD to perform special activities with the preschool classes in order to hasten the reading and written acquisition by the children clearing opposing to what the legal guidelines determine (BRASIL, 2009). The interviews show that, from the teachers’ perspective, the work of the PD is of great relevance in any stage or teaching modality, and that in the nursery it translates into a cooperative action, and assistance to teachers in the formative, directive and care dimensions. However, they consider that in the researched ECEU this action is crossed by an accumulation of tasks that makes distant the PD from the follow-up of the teachers in their work with the children. In evaluating her own work, the CP PD stated that she has a feeling of dissatisfaction for not being able to carry out all the actions that she would like. However, she considers that in spite of the many challenges, along with her team she seeks ways of performing a committed work with the children as a sign of resistance and daily struggle in the institution. The analysis of the collected data has indicated a necessity of a greater support to managerial centers of institutions of Early Childhood Education, including to expand the team for offering better conditions for the PD to carry out a work with the teachers aiming to guarantee the right of the babies and fairly small children of having a public education and with quality.